A Pedagogical Virtual Reality Environment for Children in Early Childhood Education - de Oliveira, Raquel E. M.; Ferreira, Lorran R.; de Oliveira, Jauvane C. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
The research presented here describes the use of a virtual reality system focused on the teaching-learning process in early childhood education. The system comprises of four activities that aim at developing and improving skills related to perception, motor coordination, recognition of geometric shapes, and spatial location and orientation. The interaction with the virtual environment occurs through Kinect360, enabling three-dimensional tracking of the students body in real time. The SUS evaluation method was administered to pedagogues to assess the usability of the system, and the results obtained are satisfactory and give evidence of the applicability of the system.